Measuring. Monitoring. Management. Control - Yu.M. Scryabin (Измерение, мониторинг, управление, контроль)
Background. This research relates to the field of aircraft location using an information and measurement system of electrostatic location. To locate aircraft, it is necessary to determine the signs of an electrostatic signal from several sensors. Depending on the signal-to-noise ratio, the signs are determined with an error that affects the error in determining the coordinates of the UAV. Materials and methods. A mathematical model of the operation of the electrostatic location system was used to analyze the error. The influence of the error is determined based on the method of calculating the error of indirect measurements. Results. The equations for calculating the coordinates of the UAV and their error are obtained for various combinations of flight parameters and signal/noise values. Conclusions. The error of the UAV flight can be reduced by combining the Morlaix wavelet function and the rational function as an analyzing one, as well as by using a three-row sensor layout.